2015
DOI: 10.3109/00365521.2015.1086019
|View full text |Cite
|
Sign up to set email alerts
|

Yield of endoscopic ultrasound-guided fine needle aspiration and endoscopic retrograde cholangiopancreatography for solid pancreatic neoplasms

Abstract: EUS-FNA is superior to ERCP cytology for diagnosis of solid pancreatic neoplasms. Although combination of both procedures provide efficient tissue diagnosis and with a minimal adverse events rate, a prospective study including larger number of patients is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Because agenesis of the dorsal pancreas is sometimes complicated by pancreatic tumors, such as ampullary carcinoma, 13 pancreatic neuroendocrine tumor, 14 pancreatic ductal adenocarcinoma, 15 and mucinous adenocarcinoma, 2 EUS-FNA-guided biopsy may be helpful. Malak et al 16 implied that EUS-FNA was more sensitive than ERCP cytology in diagnosing malignant pancreatic neoplasms. Each examination has its advantages; thus, a full understanding of the characteristics of each examination will be beneficial for correct diagnosis of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because agenesis of the dorsal pancreas is sometimes complicated by pancreatic tumors, such as ampullary carcinoma, 13 pancreatic neuroendocrine tumor, 14 pancreatic ductal adenocarcinoma, 15 and mucinous adenocarcinoma, 2 EUS-FNA-guided biopsy may be helpful. Malak et al 16 implied that EUS-FNA was more sensitive than ERCP cytology in diagnosing malignant pancreatic neoplasms. Each examination has its advantages; thus, a full understanding of the characteristics of each examination will be beneficial for correct diagnosis of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Malak et al. 16 implied that EUS-FNA was more sensitive than ERCP cytology in diagnosing malignant pancreatic neoplasms. Each examination has its advantages; thus, a full understanding of the characteristics of each examination will be beneficial for correct diagnosis of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…5 Another study reported that the sensitivity of ENPD cytology for detecting malignancy in patients with pancreatic carcinomas measuring ≤20 mm was 83%. 26 Regarding the diagnosis of malignancy in patients with pancreatic carcinoma, Malak et al 39 reported sensitivity, specificity, and accuracy rates of 98.9%, 93.3%, and 98.1% for EUS-FNA, compared with 72.1%, 60%, and 71.4% for ERCP, suggesting that the diagnostic ability of EUS-FNA is significantly superior to that of ERCP. However, as mentioned above, EUS-FNA is limited for the diagnosis of pancreatic carcinomas measuring ≤ 10 mm.…”
Section: Ercpmentioning
confidence: 99%
“…When deployed for distal CBD strictures, stenting via ERCP is successful in more than 90% of cases [115]. For diagnostic yield from ERCP-guided FNA of biopsies of solid pancreatic neoplasms, ERCP demonstrated sensitivity between 57.1% (for pancreatic body/tail neoplasms) and 82.4% (for pancreatic head neoplasms) [116].…”
Section: Usmentioning
confidence: 99%